Biosemiotics of Water in the Quran Surah Al-Anbiya' Verse 30 - Chaer, Hasanuddin; Sirulhaq, Ahmad; Rasyad, Abdu; Malik, Djamil Abdurachman (Universitas Airlangga, 2023)
Biosemiotics delves into the examination of meaning, communication, and signs within every living microorganism. This research endeavors to interpret the Qur'anic passage